Effectiveness of kangaroo and nesting method on body temperature of low birth weight (LBW) babies in the perinatology room - Sitti Hasriani; Roni Roni; Muhammad Tahir; Nur Laela; Ardina Sinta (Indonesian Public Health-Observer Information Forum (IPHORR) Kerjasama dengan Persatuan Perawat Nasional Indonesia (PPNI), 2025)
Background: Low birth weight (LBW) is a condition in which a baby is born weighing less than 2500 grams. Low birth weight, a leading cause of neonatal mortality, is caused by unstable body temperature. Purpose: to determine the effectiveness of the kangaroo and nesting methods on the body temperature of low birth weight infants in the Perinatology. Method: This study used a quasi-experimental method and was conducted from March to April 2025. The sample consisted of 32 infants treated in the Perinatology Unit of KH. Hayyung Regional General Hospital, Selayar Islands Regency, from March to April 2025, using accidental sampling. Results: The study showed that the kangaroo and nesting methods were effective in increasing body temperature in low birth weight infants, as indicated by a p-value <0.05. Conclusion: This means that the kangaroo and nesting methods significantly influence the body temperature of low birth weight infants. Suggestion: It is hoped that mothers who give birth to low-birth-weight babies will be able to use the kangaroo method and nesting methods in newborn care to maintain a stable body temperature